2017
DOI: 10.1136/bmjgh-2017-000508
|View full text |Cite
|
Sign up to set email alerts
|

Variations in disability and quality of life with age and sex between eight lower income and middle-income countries: data from the INDEPTH WHO-SAGE collaboration

Abstract: BackgroundDisability and quality of life are key outcomes for older people. Little is known about how these measures vary with age and gender across lower income and middle-income countries; such information is necessary to tailor health and social care policy to promote healthy ageing and minimise disability.MethodsWe analysed data from participants aged 50 years and over from health and demographic surveillance system sites of the International Network for the Demographic Evaluation of Populations and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 35 publications
2
38
1
Order By: Relevance
“…Disability was measured using the 12-item WHO Disability Assessment Schedule, version 2 (WHODAS V.2.0) disability score 11 48. This score measures impairments in function, activity and participation (mobility, self-care, cognition, interaction with others, life activities and social participation).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disability was measured using the 12-item WHO Disability Assessment Schedule, version 2 (WHODAS V.2.0) disability score 11 48. This score measures impairments in function, activity and participation (mobility, self-care, cognition, interaction with others, life activities and social participation).…”
Section: Methodsmentioning
confidence: 99%
“…Measures were summed to form a score, then normalised to a 0–100 scale, where 0 equals no disability and 100 represents the worst disability. Quality of life was measured using the validated EuroHIS 8-item version of the WHO Quality of Life (WHOQOL) 11 49. Each item was scored on a five-point scale and summed: for the analysis, the score was normalised to a 0–100 scale, with 100 denoting the best quality of life.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As underlined by some authors, [36] it is always difficult, in multicenter studies, to interpret possible differences among countries, since different response styles, differences in the meaning of response levels within the various language versions of the questionnaires or, cultural variables, play a possible role in molding the impact on the people's perception of their own QoL and LoF. In agreement with this, data from the European ESEMeD study have shown that among 1659 respondents aged ≥75 years recruited from Belgium, France, Germany, Italy, Netherlands, and Spain, there were significant differences between countries with the lowest QoL scores in Italy and the highest in the Netherlands, although it was not possible to completely understand the reasons for these differences, due to the many variables involved including the different health organizational systems in the countries [17].. On the other hand, significant differences in QoL and LoF, as ascertained by using the WHO-QoL-BREF and the WHODAS II, were also found between Asian and African countries, [37] as well as in low-income countries, with differences not fully explained by age, socioeconomic status, marital status, education or other health factors [38]. However, the data call for attention at the European Union about the need for governmental policies in order to provide more homogeneous health care to the population that is aging amongst the different countries members.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, two analytical strategies have prevailed. First, the disability is modeled in a continuum range (capture by the WHODAS score), in which higher scores represent a higher level of disability (26,27). Second, a cutoff is applied to the WHODAS score (using the 90th percentile) to generate a dichotomous variable indicating disability (18,28).…”
Section: Introductionmentioning
confidence: 99%